The effect of training and work experience on performance: The mediating role of competence at PT Chandra Asri Pacific - Feryanto, Muslim; Mulyanti, Rita Yuni; Soma, Abdul Mukti (Goodwood Publishing, 2025)
Purpose: This study investigates the direct and indirect effects of training and work experience on employee performance, with competence serving as a mediating variable in the Marine Division of PT Chandra Asri Pacific. Methodology: Using a quantitative approach, data were collected from all 66 employees through structured questionnaires and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). Validity, reliability, and mediation tests ensured robust findings. Results: The results show that work experience and competence significantly influence employee performance directly, while training has no direct effect. However, training enhances competence, which fully mediates its impact on performance. Work experience also affects performance indirectly through competence, indicating partial mediation. The model demonstrates strong explanatory (R² = 0.616) and predictive (Q² > 0.34) power. Conclusions: Competence is the central mechanism translating training and experience into performance outcomes. Training is only effective when it strengthens competence, whereas work experience contributes both directly and indirectly. Limitations: The study’s scope is restricted to a single division with a male-dominated workforce, a cross-sectional design, and exclusive use of quantitative methods, limiting generalizability and contextual depth. Contribution: Theoretically, this research validates competence as a mediator in human capital development. Practically, it highlights the importance of aligning training with competence-building, leveraging experiential learning, and implementing structured HR strategies to strengthen performance in safety-critical industrie.